Phosphate-Binding Agents in Adults With CKD: A Network Meta-analysis of Randomized Trials - Palmer, Suetonia C.; Gardner, Sharon; Tonelli, Marcello; Mavridis, Dimitris; Johnson, David W.; Craig, Jonathan C.; French, Richard; Ruospo, Marinella; Strippoli, Giovanni F.M. (American journal of kidney diseases, 2016)
Guidelines preferentially recommend noncalcium phosphate binders in adults with chronic kidney disease (CKD). We compare and rank phosphate-binder strategies for CKD. Network meta-analysis. Adults with CKD. Randomized trials with allocation to phosphate binders. Sevelamer, lanthanum, iron, calcium, colestilan, bixalomer, nicotinic acid, and magnesium. The primary outcome was all-cause mortality. Additional outcomes were cardiovascular mortality, myocardial infarction, stroke, adverse events, serum phosphorus and calcium levels, and coronary artery calcification. 77 trials (12,562 participants) were included. Most (62 trials in 11,009 patients) studies were performed in a dialysis population. Trials were generally of short duration (median, 6 months) and had high risks of bias. All-cause mortality was ascertained in 20 studies during 86,744 patient-months of follow-up. There was no evidence that any drug class lowered mortality or cardiovascular events when compared to placebo. Compared to calcium, sevelamer reduced all-cause mortality (OR, 0.39; 95% CI, 0.21-0.74), whereas treatment effects of lanthanum, iron, and colestilan were not significant (ORs of 0.78 [95% CI, 0.16-3.72], 0.37 [95% CI, 0.09-1.60], and 0.55 [95% CI, 0.07-4.43], respectively). Lanthanum caused nausea, whereas sevelamer posed the highest risk for constipation and iron caused diarrhea. All phosphate binders lowered serum phosphorus levels to a greater extent than placebo, with iron ranked as the best treatment. Sevelamer and lanthanum posed substantially lower risks for hypercalcemia than calcium. Limited testing of consistency; short follow-up. There is currently no evidence that phosphate-binder treatment reduces mortality compared to placebo in adults with CKD. It is not clear whether the higher mortality with calcium versus sevelamer reflects whether there is net harm associated with calcium, net benefit with sevelamer, both, or neither. Iron-based binders show evidence of greater phosphate lowering that warrants further examination in randomized trials.